Robust stability of reset control systems with uncertain output matrix - Guo, Yuqian (2013)
The main difficulty in stability analysis of reset control systems comes from their state-dependent reset mechanism. It becomes more challenging when output matrix suffers from uncertainties which make the reset time instants uncertain. In this paper, existing quadratic stability results for uncertainty-free reset systems are extended to the case with uncertainty in the output matrix. By constructing special parameter-dependent full rank annihilators of the output matrix, it is proved that the dissipativeness of reset action is equivalent to the feasibility of an LMI plus some structural constraints on the Lyapunov matrix. For the time-varying uncertainty case, necessary and sufficient conditions for quadratic stability are obtained. For the constant uncertainty case, a sufficient condition for affine quadratic stability is also obtained. All the results are given in terms of LMIs which can be efficiently verified.